2022
DOI: 10.1186/s12889-022-13990-4
|View full text |Cite
|
Sign up to set email alerts
|

Being silenced, loneliness and being heard: understanding pathways to intimate partner violence & abuse in young adults. a mixed-methods study

Abstract: Background International research shows the significance and impact of intimate partner violence and abuse (IPVA) as a public health issue for young adults. There is a lack of qualitative research exploring pathways to IPVA. Methods The current mixed-methods study used qualitative interviews and analysis of longitudinal cohort data, to explore experiences of pathways to IPVA. Semi-structured Interviews alongside Life History Calendars were undertak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…The effects of DV on children's wellbeing and social development have been widely researched and documented (Barnes et al, 2022;Campo, 2015;Forke, 2019;Graham-Bermann et al, 2009;Øverlien, 2017). Further, it is recognised that children raised in DV can face psychosocial challenges and developmental hurdles because of their childhood experiences (Fellin et al, 2019).…”
Section: Outcomes Of Growing Up With DVmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of DV on children's wellbeing and social development have been widely researched and documented (Barnes et al, 2022;Campo, 2015;Forke, 2019;Graham-Bermann et al, 2009;Øverlien, 2017). Further, it is recognised that children raised in DV can face psychosocial challenges and developmental hurdles because of their childhood experiences (Fellin et al, 2019).…”
Section: Outcomes Of Growing Up With DVmentioning
confidence: 99%
“…Further, Kitzmann et al (2003), in their seminal meta-analytical review, analysed 118 studies of children exposed to DV and found that 33% of the children had wellbeing scores comparable with, or better than, other children. Children's ages, gender, coping abilities and supports in the societal context have been found to influence the outcomes associated with growing up in DV (Barnes et al, 2022;Clements et al, 2008;Yule et al, 2019). Research indicates that the extent to which children are able to cope with DV is linked to their mothers' capacity to maintain close relationships and protect their children as well as they can (Buchanan, 2018;Winfield et al, 2023).…”
Section: Outcomes Of Growing Up With DVmentioning
confidence: 99%
“…The reasons for nondisclosure of sexual violence among children have been investigated for some time (Alaggia et al, 2019; Reitsema & Grietens, 2016; Tener & Murphy, 2015). These include studies that address the process and pathways of disclosure (Alaggia, 2010; Barnes et al, 2022; Staller & Nelson‐Gardell, 2005) and identify barriers to disclosure such as stigma and shame (Delker et al, 2020; Halvorsen et al, 2020; Kennedy & Prock, 2018; Morrison et al, 2018; Verelst et al, 2014). Recent investigations have explored adult survivors' perspectives (Solberg et al, 2021) and young people's perspectives (Landberg et al, 2022) as well as the perspectives of parents whose children have disclosed sexual violence (McElvaney & Nixon, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Since 2017, the international Metoo movement has contributed to freeing women's voices about sexual violence [1][2][3]. However, domestic or sexual violence is still difficult to verbalize for survivors and associated with a lack of social and emotional support [4][5][6][7]. A controlled trial in the US showed that following sexual assault, survivors were more reduced to silence and stigmatized than after physical violence [8].…”
Section: Introductionmentioning
confidence: 99%